Advertising jewelry - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
Jewelry carries a variety of cultural meanings in the international market. This case study considers the adaptations that must be made when marketing jewelry in the international business environment.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Advertising Jewelry. In International marketing (pp. 441-442). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Advertising -- Jewelry -- Case studies; Export marketing -- Case studies